Activation of hedgehog signaling during fracture repair enhances osteoblastic‐dependent matrix formation. Issue 4 (17th December 2013) - Baht, Gurpreet S; Silkstone, David; Nadesan, Puviindran; Whetstone, Heather; Alman, Benjamin A
ABSTRACT Fracture repair is a well orchestrated process involving various cell types and signaling molecules. The hedgehog signaling pathway is activated in chondrocytes during fracture repair and is known to regulate chondrogenesis however, its role in osteoblasts during injury is yet unknown. In this study we observed tibial fracture repair in mice in which hedgehog signaling was modulated through genetic alterations of the pathway activator, smoothened. Levels of the hedgehog target genes Gli1 and Ptch1 in wildtype mice were upregulated in fracture calluses throughout the repair process. Forced activation of the hedgehog pathway in ubiquitous fashion resulted in increased matrix deposition in the fracture callus. Interestingly, inhibition in chondrocytes did not alter the fracture repair phenotype, while activation of hedgehog in osteoblasts was a requirement for normal fracture repair. In vitro, transcript levels of Gli1 and Ptch1 were elevated during osteoblastogenesis. Activation of hedgehog signaling positively affected osteoblastic differentiation and mineralization as detected using alkaline phosphatase and Von Kossa staining and Alp and Col1 expression. Here we show that the hedgehog signaling pathway plays a critical role in osteoblasts during fracture repair: inhibition of the pathway in osteoblasts leads to decreased matrix at the fracture site while activation increased matrix deposition.© 2013 The Authors. Orthopaedic Research published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society © 2013 The Authors. Published by Wiley Periodicals, Inc. on behalf of the Orthopaedic Research Society. J Orthop Res J Orthop Res 32:581–586, 2014.